2019
DOI: 10.1111/ejn.14567
|View full text |Cite
|
Sign up to set email alerts
|

Towards a standard model of musical improvisation

Abstract: Musical improvisation is a sophisticated cognitive process that combines creativity, goal‐directed action, sensory monitoring and social interaction. With a renewed interest in quantifying creative processes facilitated by recent advances in neuroimaging technology, musical improvisation has emerged as an ideal paradigm to study creativity. However, many studies isolate the top‐down processes related to creativity from those related to production and auditory perception, leaving the question of how creative be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
4
0
3
Order By: Relevance
“…Recent neuroimaging studies on musical improvisation have identified brain regions and networks involved in musical improvisation and other creative domains such as literacy and drawing. As reviewed in contemporary literature [1][2][3], variations in brain activity and connectivity may be related to the heterogeneity of the participant's background, their learned skills, experience, and creative expertise. In a recent neuroimaging study of advanced jazz musicians, we explored the divergent brain activation and connectivity patterns during musical improvisation and non-improvisation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies on musical improvisation have identified brain regions and networks involved in musical improvisation and other creative domains such as literacy and drawing. As reviewed in contemporary literature [1][2][3], variations in brain activity and connectivity may be related to the heterogeneity of the participant's background, their learned skills, experience, and creative expertise. In a recent neuroimaging study of advanced jazz musicians, we explored the divergent brain activation and connectivity patterns during musical improvisation and non-improvisation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Esta produciría una preferencia ante estímulos inesperados que puede ser un factor determinante del desempeño creativo de un sujeto (Przsysinda et al, 2017). Estos hallazgos suman evidencia a la idea de que analizar la improvisación musical es sumamente útil para el estudio de la creatividad humana (Biasutti, 2015;Faber y McIntosh, 2020).…”
Section: Discussionunclassified
“…La improvisación musical involucra procesos creativos, pero no es sinónimo de creatividad. Por un lado, es un proceso cognitivo sofisticado que involucra otros elementos además de la creatividad: acción dirigida a objetivos, funciones ejecutivas, monitoreo sensorial y feedback, y variables contextuales como la interacción social (Faber y McIntosh, 2020). Y por el otro, la creatividad implica una capacidad de creación de productos novedosos de diversas modalidades, no únicamente musicales o auditivas (Torrance, 1965).…”
Section: Improvisación Musicalunclassified
See 1 more Smart Citation
“…Following from definitions of creativity in the psychology literature, improvisation can be characterized as the spontaneous formation of novel, high quality output, that is novel and useful (Sternberg et al, 2004). Recent work has begun to coalesce knowledge and models from electroencephalography (EEG) studies (Stevens Jr & Zabelina, 2019), the involvement of the motor system (Bashwiner & Bacon, 2019), the importance of expertise (Pinho et al, 2014;Braun, 2008), perception-action coupling (Loui, 2018), top-down and bottom-up networks (Faber & McIntosh, 2020), and network neuroscience (Beaty et al, 2019;Belden et al, 2020).…”
mentioning
confidence: 99%